Benefits of using a tax refielf forR&D works. - Oliwkiewicz, Barbara; Łojek, Paweł (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Research and development works (RD works) in accounting and management are increasingly being implemented and used, both in Poland and around the world. The legislator is constantly trying to introduce new benefits into the legal system in the form of tax breaks. However, as shown in the article, respondents (accountants, managers, beneficial owners) have low awareness and knowledge of possible solutions. The article aims to verify research hypotheses through chi-square tests of independence. The research questions regarding the relationship between the length of service and the position held, the position held and the knowledge of the combined (simultaneous) tax relief, as well as the relationship between the impact of the simultaneous tax relief and the respondents' suggestions regarding potential legal changes in its scope, were verified using hypotheses. research. The conducted research contributes to a current look at the work of RD, increasing the awareness of accountants and managers, and may also constitute the basis for the development and drawing of more reliable results in the future, assuming greater return of surveys.